Geriatric ocular trauma and mortality: A retrospective cohort study - Vincent Q. Pham; Hannah M. Miller; Elise O. Fernandez; Daniel de Marchi; Elizabeth Budi; Hongtu Zhu; David Fleischman (PLoS ONE, 2025)
Purpose The objective of this investigation is to evaluate the 5-year mortality of geriatric patients who have sustained eye injuries. Design This retrospective cohort study included patients aged 65 years or older who had histories of either ocular trauma or age-related nuclear cataracts. Subjects and controls: Patients with ocular trauma constituted the study group, while those with a history of cataracts served as controls. Methods Data from the I2B2 Carolina Data Warehouse were analyzed. Patient demographics were collected, and the outcomes of interest were the overall mortality rate and annual mortality rates over a 5-year period. Chi-squared tests were utilized for the comparison of mortality data. Main outcomes and measures The primary outcomes were overall mortality rates and annual mortality rates expressed as percentages. Results The study group consisted of 602 patients who had suffered ocular trauma. The control group included 1066 patients of similar age who had been diagnosed with age-related nuclear cataracts at some point in their lives. Among the study group, 74 patients died within 5 years, while 69 patients in the control group died within the same timeframe, resulting in a study group mortality rate of 11.30% and a control group mortality rate of 6.47%. For patients with ocular trauma, the annual mortality rates were 4.15%, 2.60%, 1.96%, 2.54%, and 0.56%, respectively. For the control group, the annual mortality rates were 1.03%, 1.70%, 1.64%, 0.88%, and 1.38% respectively. Conclusion The study suggests that geriatric patients who have experienced ocular trauma are at a higher risk of mortality compared to age-matched controls without such injuries. These findings highlight the necessity of identifying the causes of geriatric periorbital trauma and underscore the importance of close patient follow-up to improve outcomes.